Effect of stem flattening on rotational stability of a canine femoral total hip component in polymethylmethacrylate cement - Mason, D. R.; Schulz, K. S.; Kass, P. H.; Stover, S. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
This study was designed to determine the effect of flattening the lateral aspect of a commercially available femoral prosthesis on its rotational stability in polymethylmethacrylate cement. Five standard design and five laterally flattened size 7 canine femoral components were evaluated. The stems were embedded in commercially available medical grade polymethylmethacrylate and rotated 15° while torque and angular displacement data were collected. The stiffness, yield and failure variables were compared between commercial and flattened stems. None of the mechanical testing variables were statistically different between commercial and flattened stems although all of the mean values for flattened stems were higher (1-30%) than mean values for commercial stems. Rotational stability of a canine total hip replacement femoral component was not significantly enhanced by the flattened component design modification evaluated by the testing protocol in this study.
Keywords: Canine; femoral stem; torsion; total hip replacement